A195 DURABILITY OF SEROLOGICAL RESPONSES AFTER SECOND, THIRD AND FOURTH DOSE OF SARS-COV-2 VACCINATION IN INFLAMMATORY BOWEL DISEASE: A PROSPECTIVE COHORT STUDY. (7th March 2023) - Sharifi, N; Ma, C; Seow, C; Quan, J; Hracs, L; Caplan, L; Markovinović, A; Herauf, M; Windsor, J; Coward, S; Buie, M; Gorospe, J; et al.
Abstract: Background: Adequate serological responses following two-dose regimens and additional doses of SARS-CoV-2 vaccination have been demonstrated for the vast majority of those with IBD. However, antibody levels following 2 nd, 3 rd, and 4 th dose SARS-CoV-2 vaccination may decrease over time in the IBD population. Purpose: We assessed the durability of serological responses to 2 nd, 3 rd, and 4 th dose SARS-CoV-2 vaccination over time in a cohort of IBD patients. Method: Adults with IBD who received at least one dose of a SARS-CoV-2 vaccine ( n =559) were evaluated for serological response to the spike protein of SARS-CoV-2 using the Abbott IgG II Quant assay with a seroconversion threshold of ≥ 50 AU/mL. The geometric mean titer (GMT) with 95% confidence intervals (CI) were calculated and stratified by weeks (1–8, 8–16, 16–24, 24+ weeks) after each vaccine dose. We compared stratified GMTs with Mann–Whitney U tests using a significance level of 0.05. Result(s): Our cohort ( n =559) comprised the following patient characteristics: 82.8% were 18–65 years-old ( n = 463), 53.1% were female ( n =297), and 71.6% had Crohn's disease ( n =400). IBD medications were classified in the following mutually exclusive groups: No immunosuppressives 10.5% ( n = 59), anti-TNF monotherapy 35.8% ( n = 200), immunomodulatory monotherapy 2.1% ( n =12 ), vedolizumab 11.8% ( n =66 ), ustekinumab 20.4% ( n =114 ), tofacitinib 1.2% ( n =7 ), combination therapy 15.9% ( n = 89), and prednisone 2.1% ( n =12). For vaccine type, 85.6% and 82.3% had Pfizer for 3 rd and 4 th dose, respectively, while the remainder had Moderna. Seroconversion rates 1–8 weeks after 3 rd and 4 th dose were both 99.9%. Figure 1 compares GMTs with 95% CI by weeks after each vaccine dose. GMTs are highest 1–8 weeks after 2 nd dose (4053 AU/mL; 95% CI: 3468, 4737 AU/mL; n =337), 3 rd dose (12116 AU/mL; 10413, 14098 AU/mL; n =256), and 4 th dose (14337 AU/mL; 10429, 19710 AU/mL; n =67). Subsequently, antibody levels decay from 1–8 weeks to 8–16 weeks ( p <0.001) for 2 nd dose (mean difference: –2224 AU/mL), 3 rd dose (mean difference: –7526 AU/mL), and 4 th dose (mean difference: –9715 AU/mL). Compared to 16–24 weeks after 2 nd dose, antibody levels 24+ weeks after were similar (GMTs: 795 AU/mL vs. 1043 AU/mL, p =0.52). For third dose, antibody levels 8–16 weeks and 16–24 weeks after vaccination were similar (4590 AU/mL vs. 4073 AU/mL, p =0.73) along with 16–24 weeks compared to 24+ weeks after vaccination (4073 AU/mL vs. 5876 AU/mL, p =0.18). Image: Conclusion(s): Within 1–8 weeks after each dose of vaccine, serological responses spikes with each subsequent dose yielding a higher GMT. While antibody levels decay 8–16 weeks after each dose, similar GMT levels beyond 16 weeks may indicate durability of antibody levels over a longer duration of time. Disclosure of Interest: None Declared